Multi-criteria Group Decision Making with Picture Linguistic Numbers - Pham, Hong Phong (ĐHQGHN, 2017)
In 2013, Cuong and Kreinovich defined picture fuzzy set (PFS) which is a direct extension of fuzzy set (FS) and intuitionistic fuzzy set (IFS). Wang et al. (2014) proposed intuitionistic linguistic number (ILN) as a combination of IFS and linguistic approach. Motivated by PFS and linguistic approach, this paper introduces the concept of picture linguistic number (PLN), which constitutes a generalization of ILN for picture circumstances. For multi-criteria group decision making (MCGDM) problems with picture linguistic information, we define a score index and two accuracy indexes of PLNs, and propose an approach to the comparison between two PLNs. Simultaneously, some operation laws for PLNs are defined and the related properties are studied. Further, some aggregation operations are developed: picture linguistic arithmetic averaging (PLAA), picture linguistic weighted arithmetic averaging (PLWAA), picture linguistic ordered weighted averaging (PLOWA) and picture linguistic hybrid averaging (PLHA) operators. Finally, based on the PLWAA and PLHA operators, we propose an approach to handle MCGDM under PLN environment.